An Investigation of the Advantages and Challenges of Case-based Method in EFL Classroom - Agustiana, Sherly (STIT Buntet Pesantren Cirebon, 2023)
This research aims to investigate the implementation of the case-based method and its advantages and challenges in the EFL classroom. This research used case study design under qualitative research. The participants in this research were an English teacher and four students who were in the twelfth grade in senior high school. The instruments in this research were interview. Interview was used to investigate the implementation of the case-based method in the EFL classroom and to examine the advantages and challenges of the case-based method. The findings showed that teacher implemented case-based method in EFL classroom on discussion text learning by conducting a debate between two teams to conclude a case. The results of interview revealed that learning with case-based methods had several advantages, namely students' confidence, speaking skill, creativity, collaboration and critical thinking. In addition, the method also had challenges that teachers and students go through. The teacher and students have the same perspective on the advantages and challenges in used case-based method. Therefore, the case-based method was indeed the right teaching method to be implemented in the classroom because there were several advantages that can improve students' abilities, despite the challenges that exist.